Analysis of Science Education Curriculum for Students with Special Needs in Special Schools: The Curriculum of 2013 - Sofi Septiani Julaeha Nursaniah (Indonesian Journal of Community and Special Needs Education, 2023)
In Indonesia, the use of the education curriculum continues to grow along with the developments and demands of the times. The Curriculum of 2013 (K-13) is an update from the Curriculum of 2006 (KTSP), especially in the learning process that uses a scientific approach. In special education, the curriculum implementation is still adjusted to the students' barriers, abilities, and needs. This study aims to analyze the Curriculum of 2013 (K-13) in science education for students with special needs in terms of objectives, content, strategies, and evaluation of learning at each level. The method used is descriptive qualitative with data collection techniques in the form of observation and literature review of existing research and relevant theories. The results of the study show that the science education curriculum in special schools is differentiated based on the type of barriers, namely for children with visual impairments (blind), hearing impairments (deaf), intelligence barriers, ADHD, autism, and motor impairments. Content, learning objectives, and learning strategies are also adjusted to the types of student barriers. However, several aspects of K-13 are not by the learning rules for students with special needs, such as the strategies used in science learning for students with cognitive disabilities. Thus, teachers’ creativity is needed in implementing classroom learning. Moreover, the K-13 is not flexible enough in developing special education.